2002
DOI: 10.1108/01443330210789951
|View full text |Cite
|
Sign up to set email alerts
|

“A part of the neighbourhood?”: negotiating race in American suburbs

Abstract: Compares race relations in two suburban communities in order to show that middle‐class blacks meet with some success when they temporarily exchange their racial identity for a class‐based identity. Collects data through ethnography and individual interview to examine the conditions under which middle‐class blacks construct and assert a sub‐urban identity. States that success varies with the racial composition of the suburban community and the white neighbours’ level of the satisfaction with the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Therefore, middle class Black parents may not only intervene more often when their children experience discrimination, but they may also be more likely to intervene in ways that are considered acceptable within the school setting (Day-Vines et al, 2003). Thus, in some instances class power may mediate racial injustice or provide protection from discrimination in some contexts (hooks, 2000; Lacy, 2002). …”
Section: Racial Discriminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, middle class Black parents may not only intervene more often when their children experience discrimination, but they may also be more likely to intervene in ways that are considered acceptable within the school setting (Day-Vines et al, 2003). Thus, in some instances class power may mediate racial injustice or provide protection from discrimination in some contexts (hooks, 2000; Lacy, 2002). …”
Section: Racial Discriminationmentioning
confidence: 99%
“…Other work suggests that emphasizing different aspects of identity may also help in the transition between Black and White environments. Lacy (2002) observed that middle class Blacks sometimes distinguish themselves from other Blacks by emphasizing their class status and minimizing their racial identity in interactions with Whites. Future research should address class differences in the extent to which African Americans participate in each realm and how African American parents socialize their children to participate in different cultural realms.…”
Section: Social Class and The Accumulation Of Social And Cultural Capmentioning
confidence: 99%
“…While sociologists have been able to conduct careful analyses of racial segregation across neighborhoods, investigating social relations across racial lines within neighborhoods poses unique challenges because of suburbanites' reticence. Unlike urbanites (e.g., Anderson, ; Reider, ; Rich, ), American suburbanites tend to be “eerily silent on the topic of race” (Lacy, : 44; 2007: 232; also Baumgartner, ; Perin, ). Unsurprisingly, there have been few if any published studies that have asked suburbanites explicit questions about race relations within their own neighborhood.…”
Section: Inter‐household Exchanges and The Generation Of Social Capitalmentioning
confidence: 99%
“…It is possible that multiracial suburban neighborhoods are characterized by racism (Kefalas, ), “neutral ethnocentrism” by both blacks and whites (Clark, ), and “avoidance strategies” by suburban blacks such as opting not to acknowledge neighbors or avoiding activities that marginalize residents along racial lines (Lacy, : 56). All three interaction patterns may lead to black–white encounters being infrequent (Lacy, : 42), brief, and superficial (Sigelman, Bledsoe, Welch, and Combs, ). If this is the case, research on social capital (Bourdieu, ; Carpiano, ; Putnam, ) suggests that members of black households may not derive the same social and informational benefits of suburban residence as do whites and members of other groups.…”
Section: Introductionmentioning
confidence: 99%
“…However, we also have many examples of symbolic boundaries being employed to “contest and reframe the meaning of social boundaries” (Lamont and Molnár, 2002), as when disadvantaged groups employ boundary‐work to distinguish themselves from those still more disadvantaged than they, or when such boundary‐work serves to redefine “success” (as in Lamont, 2000). The creation of these intersubjective boundaries has also been significant for discourse on racial, class, and gender distinctions (Lacy, 2002; Lamont and Molnár, 2002).…”
Section: Boundaries and Communitiesmentioning
confidence: 99%